IDENTIFICATION OF NECROPHAGOUS FLIES IN KERANDANGAN NATURE PARK, LOMBOK - Fitri Ramadani; Budi Utomo; Yuliadi Zamroni (Universitas Airlangga, 2024)
Necrophagous flies are flesh-eating insects during the decomposition process of animal organic substances.Their diversity and abundance are influenced by environmental factors and biogeographical positions. This studyaimed to identification the diversity and abundance of necrophagous flies in Kerandangan Nature Park, Lombok. Inthis study, we used rat carcasses as food for necrophagous larvae. The results of this study obtained four Family flies,there is Calliphoridae, Sarcophagidae, Muscidae, and Piophilidae, and 12 species of necrophagous flies, they areChrysomya megacephala, Chrysomya rufifacies, Chrysomya bezziana, Calliphora sp., Lucilia sp., Hemipyrellialinguriens (Diptera: Calliphoridae), Hydrotaea ignava, Antherigona orientalis (Diptera: Muscidae), Protopiophilasp. (Diptera: Piophilidae); Sarcophaga bravicornis, Sarcophaga cf australis, and Sarcophaga cf lincta (Diptera:Sarcophagidae). The most dominant necrophagous insects present are Chrysomya megacephala and Chrysomyarufifacies.